2009
DOI: 10.1007/s12010-009-8637-5
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Soybean Seed as Protein Expression System: Aqueous Extraction of Recombinant β-Glucuronidase

Abstract: Soybean is one of the plant species with potential to be used as seed-based bioreactor. As part of the downstream processing (DSP) of this technology, extraction is a key step, since it defines the composition of the solution from which the recombinant product will be purified. In the present work, the characteristics of soybean seeds used as a bioreactor were evaluated from a process engineering standpoint through analysis of the influence of pH and ionic strength on the extraction of recombinant beta-glucuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 24 publications
2
10
0
Order By: Relevance
“…This result is presented in Figure 5, which shows that seed proteins have acidic characteristics. This characteristic was also reported by Robic et al [38]. At the peptide level (Figure 6), 22% of all database peptides have a pI of less than 5, and 25% of them have a pI between 5 and 8.…”
Section: Resultssupporting
confidence: 85%
“…This result is presented in Figure 5, which shows that seed proteins have acidic characteristics. This characteristic was also reported by Robic et al [38]. At the peptide level (Figure 6), 22% of all database peptides have a pI of less than 5, and 25% of them have a pI between 5 and 8.…”
Section: Resultssupporting
confidence: 85%
“…Experiments are currently being run that focus on improving the TSP extraction and purification protocols, such as the separation of the hFIX from abundant seed endogenous proteins, by exploring different protein solubilities in a variety of extraction buffers, among other factors. This assumption is supported by the results of our recent studies evaluating downstream processing steps involved in the purification of b-glucuronidase from transgenic soybean seeds (Robić et al 2006(Robić et al , 2010. In addition, the results reported here on homozygous soybean lines expressing the hFIX protein and those from our studies on downstream processing of transgenic soybean seeds form a foundation for the further evaluation of transgenic soybean seeds expressing hFIX and their potential economic production.…”
Section: Discussionsupporting
confidence: 83%
“…Such a theoretical scenario becomes immediately untenable if the soybean-derived therapeutic protein is destroyed following formulation from beans to a consumable. Recent success in our laboratory , and by others (Robic, Farinas, Rech, & Miranda, 2010), has demonstrated that a variety of formulations contain intact transgenic protein. While such empirical, stability studies will need to be performed with each particular transgenic protein, there are enumerable formulation strategies which have already been industrialized for soy consumables.…”
mentioning
confidence: 85%